2020
DOI: 10.7759/cureus.10314
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Hemopneumothorax in COVID-19

Abstract: A 50-year-old previously healthy male presented with fever and cough for seven days, positive for COVID-19, and was admitted to Hazm Meberik General Hospital and treated as a case of severe COVID-19 pneumonia. After improvement, he was transferred to a quarantine facility, and he later developed bilateral hemopneumothorax requiring bilateral chest tubes. Highresolution CT showed bilateral emphysematous bullous disease. Tuberculosis workup was negative, and alpha 1 anti-trypsin levels were normal. Repeated Ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The exact pathogenetic mechanism leading to spontaneous pneumothorax is not completely elucidated. However, the most probable mechanism is alveolar damage because of the inflammation and ischemic process (12)(13)(14)16). Common histopathological findings in COVID19 patients are capillary congestion and reactive pneumocyte changes indicating diffuse alveolar damage (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathogenetic mechanism leading to spontaneous pneumothorax is not completely elucidated. However, the most probable mechanism is alveolar damage because of the inflammation and ischemic process (12)(13)(14)16). Common histopathological findings in COVID19 patients are capillary congestion and reactive pneumocyte changes indicating diffuse alveolar damage (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TB is the leading cause of death from a single infectious agent. 8 Like its previous ancestors SARS-COV-1 and MERS related Coronavirus, TB-COVID-19 coinfection have been reported though data are limited. 9 As both diseases have overlapping clinical features and the same transmission mode, such co-infections are not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Salah et al suggested that complication induced cystic changes within the lung might be a reason. 20 Regarding hydrothorax, Light's criteria showed that all the effusions were exudate. These inflammatory exudates might be related to interstitial lung disease caused by COVID-19.…”
Section: Discussionmentioning
confidence: 99%